2022
DOI: 10.1146/annurev-environ-120920-015909
|View full text |Cite
|
Sign up to set email alerts
|

A New Dark Age? Truth, Trust, and Environmental Science

Abstract: This review examines the alleged crisis of trust in environmental science and its impact on public opinion, policy decisions in the context of democratic governance, and the interaction between science and society. In an interdisciplinary manner, the review focuses on the following themes: the trustworthiness of environmental science, empirical studies of levels of trust and trust formation; social media, environmental science, and disinformation; trust in environmental governance and democracy; and co-product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 141 publications
(136 reference statements)
0
15
0
Order By: Relevance
“…However, research conducted in predominantly Anglophone countries has shown that right-wing political ideology is associated with lower trust in climate scientists compared to left-wing ideology 8 . A particularly strong focus on the USA, where political gaps on climate change are large 9 , and other Western countries have resulted in a narrow geographic perspective on the relationship between political ideology and trust in climate scientists, centered on specific countries and their peculiarities 10 . This represents a significant gap in the literature, considering that findings in behavioral science from Western countries tend to have limited generalizability to other regions (e.g., 11,12 ).…”
Section: Trust In Climate Scientists and Political Ideologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, research conducted in predominantly Anglophone countries has shown that right-wing political ideology is associated with lower trust in climate scientists compared to left-wing ideology 8 . A particularly strong focus on the USA, where political gaps on climate change are large 9 , and other Western countries have resulted in a narrow geographic perspective on the relationship between political ideology and trust in climate scientists, centered on specific countries and their peculiarities 10 . This represents a significant gap in the literature, considering that findings in behavioral science from Western countries tend to have limited generalizability to other regions (e.g., 11,12 ).…”
Section: Trust In Climate Scientists and Political Ideologymentioning
confidence: 99%
“…Yet, it remains unclear whether this applies to trust in climate scientists specifically. While climate change beliefs are about an individual's stance on the existence and/or causes of climate change, trust in climate scientists is linked to the perceived expertise, credibility, and authority of the scientific community within the field of climate science 10 . Therefore, trust in climate scientists can be influenced by factors such as perceptions of scientists' ability, benevolence, competence, and integrity 41 .…”
Section: Trust In Climate Scientists and Political Ideologymentioning
confidence: 99%
“…High school students had difficulty grappling with researcher disagreements portrayed in a narrative about juvenile thyroid cancer incidence after the 2011 Fukushima Daiichi nuclear incident, although simultaneously they largely granted that disputes were a basic property of science (Hamza et al, 2022). Although concerns about alleged declines in trust in science may be overwrought-for example, see O'Neill (2002) on general problems with alleged declines in trust, and Gundersen et al (2022) on the validity of questioning scientific claims-the potential for intrascientific disputes to produce undesirable societal outcomes demands attention from risk communicators.…”
Section: Risk Communication and Scientific Disputesmentioning
confidence: 99%
“…Although concerns about alleged declines in trust in science may be overwrought—for example, see O'Neill (2002) on general problems with alleged declines in trust, and Gundersen et al. (2022) on the validity of questioning scientific claims—the potential for intrascientific disputes to produce undesirable societal outcomes demands attention from risk communicators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation